(untitled) (Proceedings of the International Conference on Education, 2020)
Performing for an audience is one of the most widely spread forms of social anxiety which affects many people, and fear is one of the most important causes of unsuccessful performance on stage. A university student – a future music teacher – experiences what it is like being in front of an audience and to feeling emotional strain. The aim of this research is to explore the ways which encourage students to feel better in front of an audience. Is it possible to overcome significant stage fright by having knowledge of psychological self-regulation? This article discloses the modelling of concert rehearsal tasks during individual lessons applying the personal meaning method (PMM): creating favourable preconditions to optimize the state of mind while on stage; strengthening the artistic suggestion of public performance of future teachers; positively influencing the learning motivation of students. Observation helped to analyze more deeply the behaviour of students and their activity in the process of training, comparing these dimensions with respective changes during public performances. PMM training verifying case method of analysis in the context of possibilities revealed the conditions of future music teachers’ regulation of emotions while on stage, ways and the peculiarities of pedagogical encouragement.